Kubični zlepki z majhno prožnostno energijo - Jaklič, Gašper (Obzornik za matematiko in fiziko, 2009)
One of the basic interpolation problems is considered. A sequence of points in the plane is given. Our goal is to find an interpolatory curve which fits the data "nicely". Cubic splines are used and a method, which minimizes the approximate strain energy of the curve. Conditions on the existence of the interpolant, which has a nice shape (it is regular, loop-, cusp- and fold-free), are derived and a simple local geometric construction is presented.
Keywords: geometrijska interpolacija; kubični zlepki; matematika; numerična analiza; prožnostna energija